Simulasi Software PVSyst 7.3 pada Rancangan Sistem PLTS On-Grid 48,4 kWp di Gedung Perpustakaan PNJ Serta Analisa Aspek Tekno-Ekonomi dan Carbon Saving - Sitorus, Andre halomoan; Hidayati, Noor; Nufus, Tatun Hayatun; Yuliana, Arifia Eka (Jurnal Mekanik Terapan, 2023)
As a public facility, the Jakarta State Polytechnic Library Building has a significant electricity demand for its operations. This electricity demand is currently fulfilled through the supply from the PLN electricity grid. The implementation of a Solar Photovoltaic System (SPV) in the Jakarta State Polytechnic Library Building can have positive impact in the long run as it does not require fuel and requires minimal maintenance. Therefore, this research conducts a simulation using PVSyst 7.3 software to design an on-grid SPV system with a capacity of 48.4 kWp for the Jakarta State Polytechnic Library Building. It also performs techno-economic analysis to assess the investment impact of its implementation and analyzes carbon saving to understand the environmental impact of the SPV system. The simulation results of the PVSyst 7.3 on-grid SPV system with a capacity of 48.4 kWp show an energy output of 68.55 MWh per year, a specific production of 1416 kWh/kWp per year, and a system efficiency of 80.36%. The techno-economic calculations of the SPV system reveal a Net Present Value of Rp. 951,624,881, an Internal Rate of Return of 9.76%, a Return of Investment of 145.54%, a Levelized Cost of Energy of Rp. 781/kWh, and a Payback Period of 9 years and 4 months. Furthermore, the carbon saving achieved from the implementation of the SPV system is equivalent to 1379 tons of CO2